Chest Wall Reconstruction for the Treatment of Lung Herniation and Respiratory Failure 1 Month after Emergency Thoracotomy in a Patient with Traumatic Flail Chest - Junepill Seok; Il Jae Wang (Journal of Trauma and Injury)
We report a case of delayed chest wall reconstruction after thoracotomy. A 53-year-old female, a victim of a motor vehicle accident, presented with bilateral multiple rib fractures with flail motion and multiple extrathoracic injuries. Whole-body computed tomography revealed multiple fractures of the bilateral ribs, clavicle, and scapula, and bilateral hemopneumothorax with severe lung contusions. Active hemorrhage was also found in the anterior pelvis, which was treated by angioembolization. The patient was transferred to the surgical intensive care unit for follow-up. We planned to perform surgical stabilization of rib fractures (SSRF) because her lung condition did not seem favorable for general anesthesia. Within a few hours, however, massive hemorrhage (presumably due to coagulopathy) drained through the thoracic drainage catheter. We performed an exploratory thoracotomy in the operating room. We initially planned to perform exploratory thoracotomy and “on the way out” SSRF. In the operating room, the hemorrhage was controlled; however, her condition deteriorated and SSRF could not be completed. SSRF was completed after about a month owing to other medical conditions, and the patient was weaned successfully.